Detection of HCMV DNA in Chronic Periodontitis Patients by Real time PCR and its relation with the severity of disease - Wasan Adnan Abid Aun; Dawood Salim Edan (College of Pharmacy / Mustansiriyah University, 2014)
Chronic periodontitis is an inflammatory disease that extends into the tissues supporting the teeth. Recent studies have demonstrated that various human herpes viruses especially human cytomegalovirus (HCMV) may play a part in the pathogenesis of human chronic periodontitis. The aim of this study is to detect HCMV DNA in saliva of chronic periodontitis patients by real time polymerase chain reaction (PCR) test, measure its copy number and find its relation with severity of the disease. The study sample consisted of fifty - three chronic periodontitis patients of both genders (27 males and 26 females) with ages ranged from 25 to 45 years and all the selected patients have not any systemic diseases. Periodontal parameters used in this study were [plaque index (PLI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment level (CAL)]. Unstimulated saliva samples were collected from all subjects and examined by real time PCR test for HCMV DNA detection. The results of this study observed that the percentage of study group who were positive for HCMV DNA was (22.6%). The present study observed that there was no relation between PLI and GI with HCMV DNA salivary level. Concerning BOP and PPD there was no relation found between BOP and PPD with HCMV DNA level. For CAL there was a significant relation found between CAL and HCMV DNA level.